TMVR after TA-TAVR: a re-redo surgery—case report - Pommert, Nina Sophie; Puehler, Thomas; Voges, Inga; Sellers, Stephanie; Lutter, Georg (Frontiers in Cardiovascular Medicine, 2024)
An 83-year-old male patient, suffering from dyspnoea and angina, was diagnosed with severe mitral valve regurgitation (MR). He had already undergone cardiac surgery in the form of coronary artery bypass grafting at the age of 64 and TA-TAVR at 79 years. After a failed attempt at mitral valve transcatheter edge-to-edge repair, he opted for TMVR. Pre-TMVR computed tomography simulation was used to analyse possible interactions between the prostheses and to predict the neo-left ventricular outflow tract (neo-LVOT). The operation was carried out without complications. There was no bleeding and the LV function remained unchanged. On MRI, the valves were perfectly aligned without any signs of paravalvular leakage or LVOT obstruction. The patient was discharged seven days postoperatively. At the one-year follow up, there was no need for rehospitalisation and the patient had clinically improved (from NYHA IV to II). Echocardiography demonstrated a mean transvalvular gradient of under 5 mmHg and no residual MR.A redo transapical access for TMVR as a tertiary cardiac operation can be easily performed. Preoperative CT suggested good alignment of the aortic and mitral valved stent which was confirmed postoperatively.